The Impact of Sand Mining on Communities Working as Lift Laborers (Study in Sunju Village, Marawola District, Sigi Regency) - Alfiska Meike Syaloomitha Ompoeo; Santi Yunus; Eko Jokolelono; Musdayati; Laendatu Paembonan (ProBisnis : Jurnal Manajemen, 2024)
This study aims to find out how mining impacts people who work as sand lifters. This research was conducted in Sunju Village. This type of research is qualitative descriptive research. Data collection techniques were done through observation, interviews, and documentation from sand lifting workers, village communities, and the Sunju Village government. The source of this research data is primary data. The results of the research show that sand miners have a positive impact on the income of sand lift workers. Along with the increasing number of orders for sand utilization from various regions, the number of orders and trucks that come in benefits miners who work as laborers, giving miners an excellent opportunity to improve the economy. The income obtained by the owner of the sand suction machine for one car truck is Rp. 130,000. The lifting workers employed by the machine owner are three to four people for each truck. The income of lifting workers every day is Rp75,000. The calculation for the monthly income of sand lifters is Rp2,250,000. The sand mine in Sunju Village also has a lot of impact on the environment and health.